Effects of Catheter-Based Renal Denervation in Hypertension: A Systematic Review and Meta-Analysis - Vukadinovic, Davor; Lauder, Lucas; Kandzari, David E.; Bhatt, Deepak L.; Kirtane, Ajay J.; Edelman, Elazer R.; Schmieder, Roland; Azizi, Michel; Böhm, Michael; Mahfoud, Felix (Circulation, 2024)
BACKGROUND: Several sham-controlled trials have investigated the efficacy and safety of catheter-based renal denervation (RDN) with mixed outcomes. We aimed to perform a comprehensive meta-analysis of all randomized, sham-controlled trials investigating RDN with first- and second-generation devices in hypertension. METHODS: We searched MEDLINE and the Cochrane Library for eligible trials. Outcomes included both efficacy (24-hour and office systolic [SBP] and diastolic blood pressure [DBP]) and safety (all-cause death, vascular complication, renal artery stenosis >70%, hypertensive crisis) of RDN. We performed a study-level, pairwise, random-effects meta-analysis of the summary data. RESULTS: Ten trials comprising 2478 patients with hypertension while being either off or on treatment were included. Compared with sham, RDN reduced 24-hour and office systolic blood pressure by 4.4 mm Hg (95% CI, 2.7 to 6.1; P<0.00001) and 6.6 mm Hg (95% CI, 3.6 to 9.7; P<0.0001), respectively. The 24-hour and office diastolic blood pressure paralleled these findings (-2.6 mm Hg [95% CI, -3.6 to -1.5]; P<0.00001; -3.5 mm Hg [95% CI, -5.4 to -1.6]; P=0.0003). There was no difference in 24-hour and office systolic blood pressure reduction between trials with and without concomitant antihypertensive medication (P for interaction, 0.62 and 0.73, respectively). There was no relevant difference in vascular complications (odds ratio, 1.69 [95% CI, 0.57 to 5.0]; P=0.34), renal artery stenosis (odds ratio, 1.50 [95% CI, 0.06 to 36.97]; P=0.80), hypertensive crisis (odds ratio, 0.65 [95% CI, 0.30 to 1.38]; P=0.26), and all-cause death (odds ratio, 1.76 [95% CI, 0.34 to 9.20]; P=0.50) between RDN and sham groups. Change of renal function based on estimated glomerular filtration rate was comparable between groups (P for interaction, 0.84). There was significant heterogeneity between trials. CONCLUSIONS: RDN safely reduces ambulatory and office systolic blood pressure/diastolic blood pressure versus a sham procedure in the presence and absence of antihypertensive medication.
CRIS-Team Scopus Importer:2024-10-18
Keywords: arterial hypertension; meta-analysis; renal denervation